Preparation and Characterization of Sr-Yig and Yig-Pva Composite - Shafie, Mohd Shamsul Ezzad (2009)
This thesis deals with the subject of magnetic properties utilizing iron garnet materials. The main purpose of this project is to prepare of Y3.0-XSrXFe5O12 and develop of YIG-PVA composite films. In addition, other properties including Q-factor, microstructure and XRD had also been studied. For powder preparation, seven garnet powder samples were prepared which are Y3.0- XSrXFe5O12 (x = 0 to 2.5), in the interest of 0.5 value. From the results, the highest permeability obtained at sample Y3.0Fe5O12 (YIG) which is 1.58. The lowest loss factor is 7.41, which is obtained from sample Y1.5Sr1.5Fe5O12. From the XRD characterization, the peak changing from 32.31° to 32.89°, indicating the transition from YIG to Strontium based iron garnet. From the SEM analysis, the Y2.0Sr1Fe5O12 has the largest grain size while Y3S0 exhibit smallest grain size. As a conclusion, this sample can be utilized for high frequencies applications. Considering the best microstructure, highest permeability, lower LF, the best sample is YIG. It was chosen as filler in preparation polymer composite. For polymer composite preparation, the composites consisted of polyvinyl alcohol (PVA) and YIG were prepared by casting technique. YIG (1 wt%) and YIG (5 wt%) prepared as filler in polyvinyl alcohol (PVA) as polymer composite. Both YIG exhibit similar XRD patterns to standard YIG sample including extra peak for PVA at 40°. Compared to YIG (1 wt%), the YIG (5 wt%) was more effective to improve the magnetic properties of the composites because of its network structure. In conclusion, a certain high level of filler content was proven to be necessary for the promotion of magnetic properties in oriented composite.